Bacteriorrodopsina: una molécula peculiar - Reyes-Martínez, Miguel A. (2005)
The bacteriorhodopsin (bR) is a protein which plays a role as a proton pump when is stimulated by light. The bR is involved in ATP's synthesis through a process of transductíon, turning light energy into chemical energy(photosynthesis). The bR codífied by bop gene and located in the cell envelope, covers up to 50 % of the extreme haloarchaeas when the environment is anaerobic. This feature shows a maximum degree of adjustment to anaerobic conditions of halophilic microorganism. Since the bR functíon as photoreceptor was proposed, several studies have been done in order to elucidate its amino acid sequence, structural conformation, physicochemical properties and expression and gene regulation characteristics. The excellent bR's photochemical and thermodynamic properties make it a peculiar molecule and a candidate to biotechnological applications in biocomputation for example in optical memories, in photoelectric systems and in biomaterials. For that reason, bR's sources of isolation and production have received a great commercial interest. In this review, the bR genesis, main function, gene expression and biotechnological application of the bacteriorhodopsin is described.